Coping Experiences: A Pathway towards Different Coping Orientations Four and Twelve Months after Myocardial Infarction—A Grounded Theory Approach - Mari Salminen-Tuomaala; Päivi Åstedt-Kurki; Matti Rekiaro; Eija Paavilainen (Nursing Research and Practice)
Background. Patients recovering from a myocardial infarction (MI) are faced with a number of serious challenges. Aim. To create a substantive theory on myocardial infarction patients’ coping as a continuum. Methods. Grounded theory method was used. Data were collected by using individual interviews. The informants were 28 MI patients. Results. The core category “coping experiences—a pathway towards different coping orientations” includes 2 main categories: “positive and negative coping experiences” (4 months after MI) and “different coping orientations” (12 months after MI). Conclusion. Coping with a myocardial infarction is a long-term dynamic process of dealing with varied emotions and adjustment needs. Coping is threatened, if the patient denies the seriousness of the situation, suffers from depression and emotional exhaustion, or if there are serious problems in the interaction with family members. This study stresses the importance of recognizing the patient’s depressive state of mind and the psychological aspects which affect family dynamics. A more family-centered approach involving a posthospital counseling intervention is recommended. Relevance to Clinical Practice. The results of this study can be used in nursing care practice when organizing support interventions for myocardial infarction patients.